A PET material capable of reflecting infrared rays and a preparation method thereof

By adding specific raw materials and modifiers to PET materials, the problems of poor flame retardant performance and poor reflected infrared performance of PET materials are solved, and the coordinated improvement of flame retardant and reflected infrared performance is achieved, and the product's cold resistance and impact resistance are improved.

CN118388936BActive Publication Date: 2025-04-25WENZHOU AOPU IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410547483.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-04-25
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

The poor flame retardant performance of existing PET materials leads to poor reflective infrared performance of the product and insufficient cold resistance and impact resistance stability, which limits the efficiency of the product.

Method used

By adding PA66, antioxidants, lubricants, flame retardants, compatibilizers, surfactants, and carbon nanotube-regulated glass fiber agents and sodium alginate modifiers to the PET material, the mutual coordination of raw materials is optimized and the flame retardant efficiency and reflective infrared performance of the product are improved.

Benefits of technology

The coordinated improvement of flame retardant and reflected infrared properties of PET materials is achieved, and the product's cold resistance and impact resistance are improved, thereby improving the product's use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004823132020000151
    Figure BDA0004823132020000151
Patent Text Reader

Abstract

The invention discloses a PET material capable of reflecting infrared rays, the PET material comprising the following raw materials in parts by weight: 45-50 parts of PET, 10-15 parts of PA66, 2-5 parts of antioxidant, 2-5 parts of lubricant, 4-7 parts of flame retardant, 1-2 parts of compatibilizer, and 2-4 parts of surfactant. The PET material of the invention adopts PET and PA66 raw materials, and by adding antioxidants, lubricants, compatibilizers, surfactants, and flame retardants, the processing effect of the product is optimized and the flame retardant efficiency of the product is improved through the mutual coordination between the raw materials. At the same time, the glass fiber agent adjusted by carbon nanotubes and the sodium alginate modifier are coordinated with each other and work together, so that the infrared reflection and flame retardant properties of the product are coordinated and improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PET materials, and in particular to a PET material capable of reflecting infrared rays and a preparation method thereof. Background Art

[0002] PET plastic is the abbreviation of Polyethylene terephthalate, referred to as PET or PETP; the Chinese meaning is: polyethylene terephthalate plastics, mainly including polyethylene terephthalate PET and polybutylene terephthalate PBT. Polyethylene terephthalate is also commonly known as polyester resin.

[0003] The existing PET materials have poor flame retardant properties. In order to enhance the flame retardant properties, inorganic flame retardants are added, which easily leads to poor interface compatibility of the product raw materials, resulting in poor infrared reflection performance of the product. It is difficult to achieve coordinated improvement of the product's infrared reflection and flame retardant properties, and the product's cold resistance and impact resistance stability are poor, further limiting the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a PET material capable of reflecting infrared rays and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a PET material capable of reflecting infrared rays, the PET material comprising the following raw materials in parts by weight:

[0007] PET 45-50 parts, PA66 10-15 parts, antioxidant 2-5 parts, lubricant 2-5 parts, flame retardant 4-7 parts, compatibilizer 1-2 parts, surfactant 2-4 parts.

[0008] Preferably, the compatibilizer is PP-g-MAH;

[0009] The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate;

[0010] The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:1.

[0011] Preferably, the PET material further comprises 4-7 parts of a glass fiber agent adjusted by carbon nanotubes and 3-5 parts of a sodium alginate modifier.

[0012] Preferably, the preparation method of the carbon nanotube-regulated glass fiber agent is:

[0013] S01: irradiating the carbon nanotubes in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W. After the irradiation, the carbon nanotubes are placed in a 3-5 times mass fraction 10% sodium lignin sulfonate solution and stirred evenly to obtain a carbon nanotube solution;

[0014] S02: 2-5 parts of stearic acid, 1-3 parts of nano-silica sol and 4-7 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid;

[0015] S03: 4-7 parts of glass fiber, 3-5 parts of 5% by mass lanthanum chloride solution, and 2-4 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier;

[0016] S04: The glass fiber modifier and the carbon nanotube regulating liquid are ball-milled at a weight ratio of 5:2, and the blending is completed by secondary ball milling. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent regulated by carbon nanotubes.

[0017] Preferably, the mass fraction of the yttrium nitrate solution is 4-7%.

[0018] Preferably, the primary ball milling process is carried out at a rotation speed of 1000-1500 r / min for 2-4 h, and the secondary ball milling process is carried out at a rotation speed of 750-950 r / min for 1-2 h.

[0019] Preferably, the preparation method of the sodium alginate modifier is:

[0020] S11: the flaky talc is firstly stirred in a sufficient amount of 10% by mass potassium permanganate solution for uniform treatment, and then washed with water and dried to obtain a talc modifier;

[0021] S12: 4-7 parts of dry talcum powder modifier, 5-10 parts of sodium silicate solution, 2-4 parts of sodium alginate and 2-5 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

[0022] Preferably, the mass fraction of the sodium silicate solution is 10-15%.

[0023] Preferably, the rotation speed of the blending and modification treatment is 550-750 r / min, the stirring time is 35-45 min, and the blending and modification temperature is 48-52°C.

[0024] The present invention also provides a method for preparing a PET material capable of reflecting infrared rays, comprising the following steps:

[0025] Step 1, stirring and mixing the raw materials at a speed of 650-750 r / min for 35-45 min, and obtaining a primary agent after the mixing is completed;

[0026] Step 2: The primary agent is then fed into a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C., and the PET material of the present invention can be obtained.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The PET material of the present invention adopts PET and PA66 raw materials, and by adding antioxidants, lubricants, compatibilizers, surfactants, and flame retardants, the processing effect of the product is optimized and the flame retardant efficiency of the product is improved through the mutual coordination between the raw materials. At the same time, the glass fiber agent adjusted by carbon nanotubes and the sodium alginate modifier are coordinated with each other and work together to improve the infrared reflection and flame retardant properties of the product. The glass fiber agent adjusted by carbon nanotubes adopts carbon nanotubes to be irradiated in a proton irradiation box before being irradiated, and then mixed with sodium lignin sulfonate solution to optimize the activity efficiency and dispersion of the carbon nanotubes. At the same time, the modified additive obtained by blending stearic acid, nano silica sol and yttrium nitrate solution adopts the mutual coordination of raw materials. , together with the adjustment liquid obtained by combining with the carbon nanotube liquid, it can enhance the modification coordination effect with the glass fiber modifier. At the same time, glass fiber, 5% by mass lanthanum chloride solution, and sodium carboxymethyl cellulose are blended and coordinated to further enhance the coordination effect of carbon nanotubes and glass fiber, improve the flame retardant and infrared reflection coordination effect of the product, and enhance the cold resistance and impact resistance of the product. At the same time, the sodium alginate modifier adopts flaky talcum powder treated with potassium permanganate solution to optimize its activity, and then blended and modified with sodium silicate solution, sodium alginate and citric acid, so as to further enhance the coordination effect of sodium alginate modifier and glass fiber agent adjusted by carbon nanotubes, thereby further improving the performance of the product. DETAILED DESCRIPTION

[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present embodiment provides a PET material capable of reflecting infrared rays, wherein the PET material comprises the following raw materials in parts by weight:

[0031] PET 45-50 parts, PA66 10-15 parts, antioxidant 2-5 parts, lubricant 2-5 parts, flame retardant 4-7 parts, compatibilizer 1-2 parts, surfactant 2-4 parts.

[0032] The compatibilizer in this embodiment is PP-g-MAH;

[0033] The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate;

[0034] The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:1.

[0035] The PET material of this embodiment also includes 4-7 parts of a glass fiber agent adjusted by carbon nanotubes and 3-5 parts of a sodium alginate modifier.

[0036] The preparation method of the glass fiber agent adjusted by carbon nanotubes in this embodiment is:

[0037] S01: irradiating the carbon nanotubes in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W. After the irradiation, the carbon nanotubes are placed in a 3-5 times mass fraction 10% sodium lignin sulfonate solution and stirred evenly to obtain a carbon nanotube solution;

[0038] S02: 2-5 parts of stearic acid, 1-3 parts of nano-silica sol and 4-7 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid;

[0039] S03: 4-7 parts of glass fiber, 3-5 parts of 5% by mass lanthanum chloride solution, and 2-4 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier;

[0040] S04: The glass fiber modifier and the carbon nanotube regulating liquid are ball-milled at a weight ratio of 5:2, and the blending is completed by secondary ball milling. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent regulated by carbon nanotubes.

[0041] The mass fraction of the yttrium nitrate solution in this embodiment is 4-7%.

[0042] In this embodiment, the rotation speed of the primary ball milling treatment is 1000-1500 r / min, and the ball milling is 2-4 hours. The rotation speed of the secondary ball milling treatment is 750-950 r / min, and the ball milling is 1-2 hours.

[0043] The preparation method of the sodium alginate modifier of this embodiment is:

[0044] S11: stirring the flaky talc powder in a sufficient amount of 10% by mass potassium permanganate solution to uniformly treat the flaky talc powder, then washing and drying the talc powder to obtain a talc powder modifier;

[0045] S12: 4-7 parts of dry talcum powder modifier, 5-10 parts of sodium silicate solution, 2-4 parts of sodium alginate and 2-5 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

[0046] The mass fraction of the sodium silicate solution in this embodiment is 10-15%.

[0047] The rotation speed of the blending and modification process in this embodiment is 550-750 r / min, the stirring time is 35-45 min, and the blending and modification temperature is 48-52°C.

[0048] The method for preparing a PET material capable of reflecting infrared rays in this embodiment comprises the following steps:

[0049] Step 1, stirring and mixing the raw materials at a speed of 650-750 r / min for 35-45 min, and obtaining a primary agent after the mixing is completed;

[0050] Step 2: The primary agent is then fed into a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C., and the PET material of the present invention can be obtained.

[0051] Example 1.

[0052] The present embodiment provides a PET material capable of reflecting infrared rays, wherein the PET material comprises the following raw materials in parts by weight:

[0053] PET 45 parts, PA66 10 parts, antioxidant 2 parts, lubricant 2 parts, flame retardant 4 parts, compatibilizer 1 part, surfactant 2 parts.

[0054] The compatibilizer in this embodiment is PP-g-MAH;

[0055] The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate;

[0056] The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:1.

[0057] The PET material of this embodiment also includes 4 parts of glass fiber agent adjusted by carbon nanotubes and 3 parts of sodium alginate modifier.

[0058] The preparation method of the glass fiber agent adjusted by carbon nanotubes in this embodiment is:

[0059] S01: irradiating the carbon nanotubes in a proton irradiation box for 5 minutes at an irradiation power of 35W, and then placing them in a 10% sodium lignin sulfonate solution with a mass fraction of 3 times and stirring them evenly to obtain a carbon nanotube solution;

[0060] S02: 2 parts of stearic acid, 1 part of nano-silica sol and 4 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid;

[0061] S03: 4 parts of glass fiber, 3 parts of 5% by mass lanthanum chloride solution, and 2 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier;

[0062] S04: The glass fiber modifier and the carbon nanotube regulating liquid are ball-milled at a weight ratio of 5:2, and the blending is completed by secondary ball milling. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent regulated by carbon nanotubes.

[0063] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0064] In this embodiment, the primary ball milling process was carried out at a rotation speed of 1000 r / min for 2 h, and the secondary ball milling process was carried out at a rotation speed of 750 r / min for 1 h.

[0065] The preparation method of the sodium alginate modifier of this embodiment is:

[0066] S11: stirring the flaky talc powder in a sufficient amount of 10% by mass potassium permanganate solution to uniformly treat the flaky talc powder, then washing and drying the talc powder to obtain a talc powder modifier;

[0067] S12: 4 parts of dry talcum powder modifier, 5 parts of sodium silicate solution, 2 parts of sodium alginate and 2 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

[0068] The mass fraction of the sodium silicate solution in this embodiment is 10%.

[0069] The rotation speed of the blending and modification process in this embodiment is 550 r / min, the stirring time is 35 min, and the blending and modification temperature is 48°C.

[0070] The method for preparing a PET material capable of reflecting infrared rays in this embodiment comprises the following steps:

[0071] Step 1, stirring and mixing the raw materials at a speed of 650r / min for 35-45min, and then obtaining a primary agent;

[0072] Step 2: The primary agent is then fed into a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C., and the PET material of the present invention can be obtained.

[0073] Example 2.

[0074] The present embodiment provides a PET material capable of reflecting infrared rays, wherein the PET material comprises the following raw materials in parts by weight:

[0075] 50 parts of PET, 15 parts of PA66, 5 parts of antioxidant, 5 parts of lubricant, 7 parts of flame retardant, 2 parts of compatibilizer, and 4 parts of surfactant.

[0076] The compatibilizer in this embodiment is PP-g-MAH;

[0077] The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate;

[0078] The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:1.

[0079] The PET material of this embodiment also includes 7 parts of glass fiber agent adjusted by carbon nanotubes and 5 parts of sodium alginate modifier.

[0080] The preparation method of the glass fiber agent adjusted by carbon nanotubes in this embodiment is:

[0081] S01: irradiating the carbon nanotubes in a proton irradiation box for 10 minutes at an irradiation power of 400 W. After the irradiation, the carbon nanotubes are placed in a 10% sodium lignin sulfonate solution with a mass fraction of 5 times and stirred evenly to obtain a carbon nanotube solution;

[0082] S02: 5 parts of stearic acid, 3 parts of nano-silica sol and 7 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid;

[0083] S03: 7 parts of glass fiber, 5 parts of 5% by mass lanthanum chloride solution, and 4 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier;

[0084] S04: The glass fiber modifier and the carbon nanotube regulating liquid are ball-milled at a weight ratio of 5:2, and the blending is completed by secondary ball milling. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent regulated by carbon nanotubes.

[0085] The mass fraction of the yttrium nitrate solution in this embodiment is 7%.

[0086] In this embodiment, the primary ball milling process was carried out at a rotation speed of 1500 r / min for 4 h, and the secondary ball milling process was carried out at a rotation speed of 950 r / min for 2 h.

[0087] The preparation method of the sodium alginate modifier of this embodiment is:

[0088] S11: stirring the flaky talc powder in a sufficient amount of 10% by mass potassium permanganate solution to uniformly treat the flaky talc powder, then washing and drying the talc powder to obtain a talc powder modifier;

[0089] S12: 7 parts of dry talcum powder modifier, 10 parts of sodium silicate solution, 4 parts of sodium alginate and 2-5 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

[0090] The mass fraction of the sodium silicate solution in this embodiment is 15%.

[0091] The rotation speed of the blending and modification process in this embodiment is 750 r / min, the stirring time is 45 min, and the blending and modification temperature is 52°C.

[0092] The method for preparing a PET material capable of reflecting infrared rays in this embodiment comprises the following steps:

[0093] Step 1, stirring and mixing the raw materials at a speed of 750 r / min for 45 min, and then completing the mixing to obtain a primary agent;

[0094] Step 2: The primary agent is then fed into a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C., and the PET material of the present invention can be obtained.

[0095] Example 3.

[0096] The present embodiment provides a PET material capable of reflecting infrared rays, wherein the PET material comprises the following raw materials in parts by weight:

[0097] PET 47 parts, PA66 12.5 parts, antioxidant 3.5 parts, lubricant 3.5 parts, flame retardant 5.5 parts, compatibilizer 1.5 parts, surfactant 3 parts.

[0098] The compatibilizer in this embodiment is PP-g-MAH;

[0099] The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate;

[0100] The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:1.

[0101] The PET material of this embodiment also includes 5.5 parts of glass fiber agent adjusted by carbon nanotubes and 4 parts of sodium alginate modifier.

[0102] The preparation method of the glass fiber agent adjusted by carbon nanotubes in this embodiment is:

[0103] S01: irradiating the carbon nanotubes in a proton irradiation box for 7.5 minutes at an irradiation power of 370W, and then placing them in a 10% sodium lignin sulfonate solution with a mass fraction of 4 times and stirring them evenly to obtain a carbon nanotube solution;

[0104] S02: 3.5 parts of stearic acid, 2 parts of nano-silica sol and 5.5 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid;

[0105] S03: 5.5 parts of glass fiber, 4 parts of 5% by mass lanthanum chloride solution, and 3 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier;

[0106] S04: The glass fiber modifier and the carbon nanotube regulating liquid are ball-milled at a weight ratio of 5:2, and the blending is completed by secondary ball milling. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent regulated by carbon nanotubes.

[0107] The mass fraction of the yttrium nitrate solution in this embodiment is 5.5%.

[0108] The rotation speed of the first-stage ball milling in this embodiment is 1250 r / min, and the ball milling is 3 h. The rotation speed of the second-stage ball milling is 800 r / min, and the ball milling is 1.5 h.

[0109] The preparation method of the sodium alginate modifier of this embodiment is:

[0110] S11: stirring the flaky talc powder in a sufficient amount of 10% by mass potassium permanganate solution to uniformly treat the flaky talc powder, then washing and drying the talc powder to obtain a talc powder modifier;

[0111] S12: 5.5 parts of dry talcum powder modifier, 7.5 parts of sodium silicate solution, 3 parts of sodium alginate and 3.5 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

[0112] The mass fraction of the sodium silicate solution in this embodiment is 12.5%.

[0113] The rotation speed of the blending and modification process in this embodiment is 600 r / min, the stirring time is 40 min, and the blending and modification temperature is 50°C.

[0114] The method for preparing a PET material capable of reflecting infrared rays in this embodiment comprises the following steps:

[0115] Step 1, stirring and mixing the raw materials at a speed of 700 r / min for 40 min, and then the mixing is completed to obtain a primary agent;

[0116] Step 2: The primary agent is then fed into a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C., and the PET material of the present invention can be obtained.

[0117] Example 4.

[0118] The present embodiment provides a PET material capable of reflecting infrared rays, wherein the PET material comprises the following raw materials in parts by weight:

[0119] PET 46 parts, PA66 12 parts, antioxidant 3 parts, lubricant 3 parts, flame retardant 5 parts, compatibilizer 1.2 parts, surfactant 3 parts.

[0120] The compatibilizer in this embodiment is PP-g-MAH;

[0121] The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate;

[0122] The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:1.

[0123] The PET material of this embodiment also includes 5 parts of glass fiber agent adjusted by carbon nanotubes and 4 parts of sodium alginate modifier.

[0124] The preparation method of the glass fiber agent adjusted by carbon nanotubes in this embodiment is:

[0125] S01: irradiating the carbon nanotubes in a proton irradiation box for 6 minutes at an irradiation power of 360W. After the irradiation is completed, the carbon nanotubes are placed in a 10% sodium lignin sulfonate solution with a mass fraction of 4 times and stirred evenly to obtain a carbon nanotube solution;

[0126] S02: 3 parts of stearic acid, 2 parts of nano-silica sol and 5 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid;

[0127] S03: 5 parts of glass fiber, 4 parts of 5% by mass lanthanum chloride solution, and 3 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier;

[0128] S04: The glass fiber modifier and the carbon nanotube regulating liquid are ball-milled at a weight ratio of 5:2, and the blending is completed by secondary ball milling. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent regulated by carbon nanotubes.

[0129] The mass fraction of the yttrium nitrate solution in this embodiment is 5%.

[0130] In this embodiment, the rotation speed of the first-stage ball milling treatment is 1200 r / min, and the ball milling is 3 hours. The rotation speed of the second-stage ball milling treatment is 780 r / min, and the ball milling is 1.2 hours.

[0131] The preparation method of the sodium alginate modifier of this embodiment is:

[0132] S11: the flaky talc is firstly stirred in a sufficient amount of 10% by mass potassium permanganate solution for uniform treatment, and then washed with water and dried to obtain a talc modifier;

[0133] S12: 5 parts of dry talcum powder modifier, 6 parts of sodium silicate solution, 3 parts of sodium alginate and 3 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

[0134] The mass fraction of the sodium silicate solution in this embodiment is 12%.

[0135] The rotation speed of the blending and modification process in this embodiment is 580 r / min, the stirring time is 38 min, and the blending and modification temperature is 50°C.

[0136] The method for preparing a PET material capable of reflecting infrared rays in this embodiment comprises the following steps:

[0137] Step 1, stirring and mixing the raw materials at a speed of 670 r / min for 38 min, and then completing the mixing to obtain a primary agent;

[0138] Step 2: The primary agent is then fed into a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C., and the PET material of the present invention can be obtained.

[0139] Comparative Example 1.

[0140] The difference from Example 3 is that no glass fiber agent adjusted by carbon nanotubes is added.

[0141] Comparative Example 2.

[0142] The difference from Example 3 is that the carbon nanotube conditioning liquid is not used in the preparation of the glass fiber agent conditioned by carbon nanotubes.

[0143] Comparative Example 3.

[0144] The difference from Example 3 is that no modifying additive is added to the carbon nanotube regulating solution.

[0145] Comparative Example 4.

[0146] The difference from Example 3 is that no nano silica sol and yttrium nitrate solution are added to the modified additive.

[0147] Comparative Example 5.

[0148] The difference from Example 3 is that no glass fiber modifier is added in the preparation of the glass fiber agent adjusted by carbon nanotubes.

[0149] Comparative Example 6.

[0150] The difference from Example 3 is that the glass fiber modifier is replaced by glass fiber.

[0151] Comparative Example 7.

[0152] The difference from Example 3 is that no sodium alginate modifier is added.

[0153] Comparative Example 8.

[0154] The difference from Example 3 is that no sodium alginate is added in the preparation of the sodium alginate modifier, and deionized water is used instead of the sodium silicate solution.

[0155] The performance of Examples 1-3 and Comparative Examples 1-8 was tested, and the cold stability was tested by placing them at -5°C for 12 hours, and the impact resistance was tested by using an impact force of 10KJ / m2 for 20 minutes. The measurement results are as follows

[0156]

[0157] From Examples 1-3 and Comparative Examples 1-8, it can be concluded that the flame retardancy and infrared reflectivity of the product of Example 3 of the present invention can be improved in a coordinated manner. At the same time, the product has a significant performance stability effect under cold resistance and impact resistance conditions. The product does not contain one of the glass fiber agent adjusted by carbon nanotubes and the sodium alginate modifier, and the performance of the product deteriorates significantly. The two are used in coordination to achieve synergistic effects.

[0158] At the same time, in the preparation of the glass fiber agent adjusted by carbon nanotubes, no carbon nanotube adjusting liquid treatment was used, no modifying additive was added to the carbon nanotube adjusting liquid, no nano-silica sol and yttrium nitrate solution were added to the modifying additive, no glass fiber modifier was added to the preparation of the glass fiber agent adjusted by carbon nanotubes, the glass fiber modifier was replaced by glass fiber, and sodium alginate was not added in the preparation of the sodium alginate modifier, and the sodium silicate solution was replaced by deionized water. The performance of the products all tended to deteriorate. The specific carbon nanotube-adjusted glass fiber agent obtained by using the method of the present invention to obtain the carbon nanotube adjusting liquid and the glass fiber modifier, and the sodium alginate modifier prepared by the method of the present invention, have the most significant performance effect of the products, and the use of other methods instead is not as obvious as the effect of the present invention.

[0159] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0160] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A PET material capable of reflecting infrared rays, characterized in that: The PET material comprises the following raw materials in parts by weight: PET 45-50 parts, PA66 10-15 parts, antioxidant 2-5 parts, lubricant 2-5 parts, flame retardant 4-7 parts, compatibilizer 1-2 parts, surfactant 2-4 parts, carbon nanotube adjusted glass fiber agent 4-7 parts, sodium alginate modifier 3-5 parts; The preparation method of the carbon nanotube-regulated glass fiber agent is as follows: S01: irradiating the carbon nanotubes in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W. After the irradiation, the carbon nanotubes are placed in a 3-5 times mass fraction 10% sodium lignin sulfonate solution and stirred evenly to obtain a carbon nanotube liquid; S02: 2-5 parts of stearic acid, 1-3 parts of nano-silica sol and 4-7 parts of yttrium nitrate solution are mixed evenly to obtain a modified additive, and the modified additive and carbon nanotube liquid are mixed evenly in a weight ratio of 2:5 to obtain a carbon nanotube regulating liquid; S03: 4-7 parts of glass fiber, 3-5 parts of 5% by mass lanthanum chloride solution, and 2-4 parts of sodium carboxymethyl cellulose are mixed and subjected to primary ball milling treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a glass fiber modifier; S04: The glass fiber modifier and the carbon nanotube conditioning liquid are subjected to ball milling treatment at a weight ratio of 5:2, and the mixed secondary ball milling is completed. After the treatment is completed, the mixture is washed with water and dried to obtain a glass fiber agent conditioned by carbon nanotubes; The preparation method of the sodium alginate modifier is: S11: the flaky talc is firstly stirred and uniformly treated in a sufficient amount of 10% by mass potassium permanganate solution, and then washed and dried to obtain a talc modifier; S12: 4-7 parts of dry talcum powder modifier, 5-10 parts of sodium silicate solution, 2-4 parts of sodium alginate and 2-5 parts of citric acid are mixed and modified. After the modification is completed, the mixture is filtered and dried to obtain a sodium alginate modifier.

2. The infrared-reflective PET material according to claim 1, characterized in that: The compatibilizer is PP-g-MAH; The antioxidant is antioxidant 1010; the lubricant is paraffin; the surfactant is sodium dodecylbenzene sulfonate; The flame retardant is a compound of melamine and magnesium hydroxide in a weight ratio of 2:

1.

3. The infrared-reflective PET material according to claim 2, characterized in that: The mass fraction of the yttrium nitrate solution is 4-7%.

4. The infrared-reflective PET material according to claim 3, characterized in that: The rotation speed of the first-stage ball milling treatment is 1000-1500r / min, and the ball milling is performed for 2-4h. The rotation speed of the second-stage ball milling treatment is 750-950r / min, and the ball milling is performed for 1-2h.

5. The infrared reflective PET material according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 10-15%.

6. The infrared-reflective PET material according to claim 5, characterized in that: The rotation speed of the blending and modification treatment is 550-750 r / min, the stirring time is 35-45 min, and the blending and modification temperature is 48-52° C.

7. A method for preparing the infrared-reflecting PET material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, stirring and mixing the raw materials at a speed of 650-750 r / min for 35-45 min, and obtaining a primary agent after the mixing is completed; Step 2: The primary agent is sent to a twin-screw extruder for melting, extrusion and granulation. The melting temperature is 190° C. to obtain PET material.

Citation Information

Patent Citations

  • Polymer material containing microencapsulated rare earth metal hypophosphite, and preparation method thereof

    CN104910591A

  • Preparation method of HDI circuit board surface film

    CN117896899A